2013
DOI: 10.1021/nl4010157
|View full text |Cite
|
Sign up to set email alerts
|

Control of Schottky Barriers in Single Layer MoS2 Transistors with Ferromagnetic Contacts

Abstract: MoS2 and related metal dichalcogenides (MoSe2, WS2, WSe2) are layered two-dimensional materials that are promising for nanoelectronics and spintronics. For instance, large spin-orbit coupling and spin splitting in the valence band of single layer (SL) MoS2 could lead to enhanced spin lifetimes and large spin Hall angles. Understanding the nature of the contacts is a critical first step for realizing spin injection and spin transport in MoS2. Here, we have investigated Co contacts to SL MoS2 and find that the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
360
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(373 citation statements)
references
References 25 publications
11
360
2
Order By: Relevance
“…13 The impact of the contact metal work function was studied in several materials. [14][15][16][17] In MoS 2 , for example, contact metals with diverse working functions ranging from 3.5 to 5.9 eV appear to all lie close to the conduction band, 14 thus suggesting Fermi level pinning by surface states. 18 The origin of this behavior needs to be understood before p-type devices can be made.…”
mentioning
confidence: 99%
“…13 The impact of the contact metal work function was studied in several materials. [14][15][16][17] In MoS 2 , for example, contact metals with diverse working functions ranging from 3.5 to 5.9 eV appear to all lie close to the conduction band, 14 thus suggesting Fermi level pinning by surface states. 18 The origin of this behavior needs to be understood before p-type devices can be made.…”
mentioning
confidence: 99%
“…After repeated peeling from the thin film, it is ultimately stamped onto a SiO 2 /Si substrate and the tape is carefully removed. Significant amount of work has been done during the early stages of nanosheet preparation [151][152][153][154] . Lee et al 65 reported isolation of single-and few layered MoS 2 films from bulk crystals of 2H-MoS 2 (SPI, natural molybdenite) using the micromechanical exfoliation method widely adopted for preparation of graphene samples.…”
Section: Micromechanical Exfoliation Methodsmentioning
confidence: 99%
“…An important device merit is the TMR ratio and much theoretical and experimental efforts have been devoted to create MTJs with different ferromagnetic metals and insulating materials in order to generate a large ratio. While materials such as MgO and Al 2 O 3 are the most popular barrier materials in practical MTJs, 16-20 2D materials graphene 21,22 and transition-metal dichalcogenides 23,24 have also been investigated in this context.Given the huge interests in 2D nano-materials and the lack of knowledge about spin injection in MBP, in this work we investigate 2D MTJs consisting of a MBP as the tunnel barrier sandwiched by Ni contacts 25 based on a state-of-the-art theoretical approach where density functional theory (DFT) 26 is combined with the Keldysh nonequilibrium Green's function (NEGF) theory. 27 We are interested in understanding the nonequilibrium spin injection property of MBP driven by a finite external bias voltage.…”
mentioning
confidence: 99%
“…An important device merit is the TMR ratio and much theoretical and experimental efforts have been devoted to create MTJs with different ferromagnetic metals and insulating materials in order to generate a large ratio. While materials such as MgO and Al 2 O 3 are the most popular barrier materials in practical MTJs, [16][17][18][19][20] 2D materials graphene 21,22 and transition-metal dichalcogenides 23,24 have also been investigated in this context.…”
mentioning
confidence: 99%